Molecular Docking of Robustaflavone Derivatives on Pi3k Protein Target and The Correlation With Its Cytotoxic Activity on Cancer Cells - Handayani, Sri; Udin, Zalinar (Indonesian Journal of Cancer Chemoprevention, 2011)
Robustaflavone Â derivatives Â have Â cytotoxic Â effect Â on Â cancer Â cell. Â Inhibition Â of Â PI3K Â onÂ cancer Â cell Â has Â correlation Â with Â apoptotic Â induction. Â The Â aim Â of Â this Â research Â is Â to Â observeÂ interaction Â from Â robustaflavone Â derivatives Â on Â PI3K Â receptor Â that Â may Â give Â contribution Â to Â theÂ cytotoxic effect of the compounds on cancer cell line. Geometric optimization of robustaflavoneÂ derivatives Â structured Â was Â done Â used Â Hyperchem Â 7.5 Â software. Â Arguslab Â 4.01 Â software Â withÂ GAdock Â method Â applied Â for Â the Â docking Â step. Â The Â docking Â result Â showed Â that Â robustaflavoneÂ 7,4,7- Â trimethyl Â ether Â (RTE) Â has Â affinity Â on Â PI3K Â target Â receptor Â which Â gave Â the Â lowest Â GibbsÂ free energy (âG -10,855 kcal/mol).Key words: robustaflavone, PI3K, cancer, docking